Adsorption performance of mangosteen shells as activated carbon to reduce heavy metals concentration in aqueous solution. - Nor Akila Akma Izanim (2014)
Pollution of the natural environment caused by heavy metal becomes a serious waste in the world especially developing country. There are many methods that had been applied to reduce the toxicity of this heavy metal such as precipitation, membrane filtration, solvent extraction and adsorption. However the adsorption method is the effective method for reduce heavy metal by using adsorbent. By using mangosteen shell as adsorbent can reduce the cost from waste disposal, reduce environmental pollution and also reduce the cost by using inexpensive material as adsorbent. The synthesis of adsorbent from mangosteen shell involved chemical activation by using Potassium hydroxide as activating agent. This study was undertaken to know the ability of mangosteen shell whether can be used as adsorbent to reduced heavy metals concentration in aqueous solution such as copper, nickel, cadmium, chromium and lead. The variation of weights and contact time are used as parameters in this research to know the effective time and amount of adsorbent that should be use for reduce the percentage of heavy metals concentration in aqueous solution. Then the effective contact time and weight of adsorbent are use to compare with silica gel for reducing heavy metals concentration in aqueous solution. From the experiment that had been done, this mangosteen shell can be used as adsorbent for reducing the percentage of heavy metals concentration in aqueous solution because it can reduce the heavy metals solution until 97% . This result that obtained by using 1.0g of adsorbent at 80 minute.